2013
DOI: 10.1007/s00402-013-1693-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia at admission is associated with in-hospital death in patients with hip fracture

Abstract: Hyponatremia at admission is prevalent in old aged patients with fracture, and is related to in-hospital death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Hyponatraemia warrants investigation and assessment as mortality risk increases with even mild derangement and is associated with increased length of hospital stay [13]. Admission hyponatraemia has been associated with increased in hospital death in hip fracture patients with an odds ratio of 3.64 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatraemia warrants investigation and assessment as mortality risk increases with even mild derangement and is associated with increased length of hospital stay [13]. Admission hyponatraemia has been associated with increased in hospital death in hip fracture patients with an odds ratio of 3.64 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical evidence have indicated in recent years that hyponatremia may negatively affect bone health [5,6,[8][9][10][11][12][15][16][17]. This study focused on the comprehension of the mechanisms leading to bone frailty in the presence of reduced [Na ? ]…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporotic fractures and their complications are a major cause of death in industrialized countries and represent a risk factor for increased mortality in both sexes [7]. Over the last few years, many studies have confirmed the association between mild chronic hyponatremia and fractures, but neurological alterations involving gait and cognitive functions only partially explain this correlation [5,6,[8][9][10][11]. On the other hand, there is now emerging literature suggesting that chronic hyponatremia represents an independent risk factor for osteoporosis by directly promoting bone loss.…”
Section: Introductionmentioning
confidence: 95%
“…Improved survival was noted in patients with a shorter time to surgery and in patients with normal cognitive status. Hyponatraemia on admission has recently been associated with in-hospital death in elderly patients admitted with hip fractures [21].…”
Section: Discussionmentioning
confidence: 99%